Public Health Nurses in Israel: A Case Study on a Quality Improvement Project of Nurse's Work Life. Issue 1 (11th March 2016) - Kagan, Ilya; Shachaf, Sara; Rapaport, Zofia; Livne, Tzipi; Madjar, Batya
Abstract: Public health nurses (PHNs) working in Well Baby Clinic in Israel's Haifa district were voicing great distress to inspectors—the impossibility of meeting their workload, feeling overwhelmed, poor physical, and technological conditions. They were feeling tired and frustrated and burn‐out was rising. The district's nursing management took the decision, together with Tel Aviv University's nursing research unit, to conduct a quality improvement project based on issues that arose from meetings with focus groups on the nurses' difficulties. This paper is a case study of a quality improvement project targeting nurses daily working life. One of its chief contributions is as a study of meeting PHNs' frustration by integrating focus groups and round‐table brainstorming (involving nurses, clinic managers and nursing inspectors) in order to identify targets for practical intervention. This strategy has been very successful. It has provided the district's nursing management a battery of forcefully argued and realistically grounded proposals for making the work of Well Baby clinics more relevant to their communities and giving nurses (a) the conditions to meet their assignments and (b) greater professional self‐respect.